웹기반 교육에 관한 연구 - 고성규; 신용철; Ko, Seong-Gyu; Shin, Yong-Cheol (대한예방한의학회지, 2007)
The Internet is increasingly changing our lives and enables the ordinary person to have access to never-ending quantities of information and knowledge. Technology and the Internet empower individuals and facilitate a more active role in the educational process. The webcast is a media file distributed over the Internet using streaming media technology and is used extensively in the commercial sector for investor relations presentations, in e-learning, and for related communications activities. And relating to computers, technology, and news are particularly popular and many new shows are added regularly. Especially e-learning is a general term used to refer to computer-enhanced learning and has the ability to level the learning playing field. So that the e-learning experience will be second nature to the growing Internet population. And this study intends to develop web-based education.